Analisis Kelayakan Finansial Pengoperasian Bus Trans Metro Dewata di Provinsi Bali - I Gede Fery Surya Tapa; I Nyoman Indra Kumara; I Ketut Sutapa; I Komang Suta Wijaya (Jurnal Ilmiah Poli Rekayasa, 2022)
Population growth that continues to increase and the ease of purchasing private cars is one factor in the increase in the number of private car owners. The government is here to change public transport services in the regions, including by operating the Trans Metro Dewata Bus in four corridors within the Sarbagita area. For now, the amount of vehicle operating costs (BOK) and operating income obtained from the operation of the Trans Metro Dewata Bus are unknown. This needs to be investigated further, especially in terms of financial feasibility. Based on the results of the study, assuming the bus fleet from the government, the total operational costs of Trans Metro Dewata Bus vehicles from 2023 - 2029, amounting to Rp.282,256,543,602. Assuming the bus fleet from the operator, the total operational cost of Trans Metro Dewata Bus vehicles from 2023 – 2029 is Rp. 391,744,920,721. The operating income based on the buy the service scheme from 2023-2029 is Rp. 366,173,491,600, while operating income based on the Tariff of Governor Regulation No. 112 of 2018 from 2023-2029 is Rp. 67,495,948,574. Based on the tariff according to Governor Regulation No. 112 of 2018 the operation of the Trans Metro Dewata Bus is not financially feasible.